Komparasi Efektivitas PAC dengan Biokoagulan Musa paradisiaca L. pada Limbah Cair Industri Tahu - Mendrofa, Cynthia Alvionie Erza; Adzillah, Wilma Nurrul; Mentari, Okti Dinasakti Nurul (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The peel of Kepok banana (Musa paradisiaca L.) can be utilized as an environmentally friendly coagulant in the treatment of tofu industry wastewater. This study examined the effectiveness of the bio-coagulant derived from Kepok banana peel in comparison to the chemical coagulant Poly Aluminium Chloride (PAC) in reducing pollutant concentrations in the tofu industry "X". The coagulation-flocculation process was conducted at laboratory scale with varying coagulant doses of 0.4 g/L, 1.2 g/L, 2 g/L, and a control test. The mixing process involved rapid stirring at 200 rpm for 5 minutes, followed by slow stirring at 40 rpm for 10 minutes, and settling for an hour. The wastewater pH was optimized to 8. The results showed that a 0.4 g/L dose of Kepok banana peel reduced BOD levels by 29.8%, COD by 58%, and TSS by 41%. For comparison, a 0.4 g/L dose of PAC demonstrated higher effectiveness, reducing BOD by 26.8%, COD by 56%, and TSS by 28%.